COOPERATIVE LEARNING STAD TYPE METHOD TO IMPROVE THE STUDENTS READING ACHIEVEMENT - Bahrun Amin (Universitas Muhammadiyah Makassar, 2012)
The objective of the research is to find out the improvement of the students’ reading achievement. It is done through cooperative learning STAD type method. It is a classroom action research at the first-grade students of SMP Kartika XX-3 Makassar. The research was conducted in two cycles in which every cycle consisted of four meetings. This research was held at the first year students of SMP KARTIKA XX-3 MAKASSAR. The subject of this research was class VII.B in 2011/2012 academic year. The students’ improvement in reading comprehension could be seen in their mean score namely 5,59 in D-test, 6,33 in cycle 1 and then it became 7,29 in cycle 11. The students’ literal reading comprehension dealing with the main idea and meaning of the word sentence in reading the text was 5, 65 in D-test 6, 44 in cycle 1 and it became 7, 65 in cycle 11. In D-test in the first meeting, the percentage of students’ activeness is 69%, and in the second meeting is 75%, and in the third meeting is 77% while in the last meeting is 82%. And then after the evaluation in the cycle II the improvement of the students’ reading comprehension. Key Word: Reading, STAD type.